Temperature-mediated Phase Transformation and Optical Properties of Tungsten Oxide Nanostructures Prepared by Facile Hydrothermal Method - Pham, Ngoc Linh; Luu, Thi Lan Anh; Nguyen, Thi Tuyet Mai; Pham, Van Thang; Nguyen, Huu Lam; Nguyen, Cong Tu (Communications in Physics, 2022)
Different tungsten oxide nanocrystals were synthesized via facile hydrothermal process – one-step and free of additives - at different reaction temperatures and a highly acidic environment. The phase transformation of samples, followed by the change of morphology and optical properties, was observed as the reaction temperature varied from room temperature to 220oC. The crystal phase transformed from monoclinic WO3∙2H2O to orthorhombic WO3∙H2O, then to monoclinic WO3 as the reaction temperature increased from room temperature to 100 ⁰C, then to 220 ⁰C. Corresponding to the phase transformation, the optical bandgap increased from 2.43 eV to 2.71 eV, and the morphology varied from nanoplate to nanocuboid. The effect of the reaction temperature on the phase transformation was assigned to the dehydration process, which became stronger as the reaction temperature increased. These results gave an insight into the phase transformation and implied a simple method for manipulating the crystal phase and morphology of tungsten oxide nanostructure for various applications.